2023
DOI: 10.5194/egusphere-egu23-17530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentially toxic element input into Mar Menor coastal lagoon (Spain) through submarine groundwater discharge

Abstract: <p><span lang="EN-US">Mar Menor, on the northern Mediterranean coast of Spain, is a coastal lagoon with a surface of 135 km<sup>2</sup>, surrounded by agriculture fields and several towns, that support an important touristic activity. In addition, mining has been an historical activity on the region. In order to elucidate the input of metals supplied by Submarine Groundwater Discharge (SGD) to the lagoon and the spatial and temporal dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…It has been reported that gene expression for DA production varies with environmental conditions [45,46]. For example, some species of Pseudo-nitzschia can produce higher levels of DA at salinities in the range found here [33], but also when lacking Fe [47,48], which is not the case as the Mar Menor is highly affected by historical mining waste [49,50], under nitrate from high groundwater discharge [51], under the limitation of Si and P [52][53][54][55], and with a varying pH [56]. The overlapping of the silicates to phosphate molar ratio (Si:P), which is an expression of phosphorous limitation against silicates used by diatoms to form its valves, suggests a positive correlation between Si:P and DA, although more data are required to confirm this hypothesis in our system.…”
Section: Domoic Acid and Environmental Variablesmentioning
confidence: 77%
“…It has been reported that gene expression for DA production varies with environmental conditions [45,46]. For example, some species of Pseudo-nitzschia can produce higher levels of DA at salinities in the range found here [33], but also when lacking Fe [47,48], which is not the case as the Mar Menor is highly affected by historical mining waste [49,50], under nitrate from high groundwater discharge [51], under the limitation of Si and P [52][53][54][55], and with a varying pH [56]. The overlapping of the silicates to phosphate molar ratio (Si:P), which is an expression of phosphorous limitation against silicates used by diatoms to form its valves, suggests a positive correlation between Si:P and DA, although more data are required to confirm this hypothesis in our system.…”
Section: Domoic Acid and Environmental Variablesmentioning
confidence: 77%